Detecting early stage osteoarthritis by optical coherence tomography?. (17th November 2015) - Jahr, Holger; Brill, Nicolai; Nebelung, Sven
Abstract: Osteoarthritis (OA) is the most common chronic disease of our joints, manifested by a dynamically increasing degeneration of hyaline articular cartilage (AC). While currently no therapy can reverse this process, the few available treatment options are hampered by the inability of early diagnosis. Loss of cartilage surface, or extracellular matrix (ECM), integrity is considered the earliest sign of OA. Despite the increasing number of imaging modalities surprisingly few imaging biomarkers exist. In this narrative review, recent developments in optical coherence tomography are critically evaluated for their potential to assess different aspects of AC quality as biomarkers of OA. Special attention is paid to imaging surface irregularities, ECM organization and the evaluation of posttraumatic injuries by light-based modalities.